SYMPTOMER OG SOCIALITET: Interview med Dorte Effersøe Gannik - Jansbøl, Kåre; Johansen, Katrine Schepelern (Tidsskriftet Antropologi, 2008)
Dorte Effersøe Gannik’s book Social Theory of Disease: A Situational Perspective is the revised version of her doctoral thesis in medical sociology. In the book, Gannik uses empirical research on backaches to construct a general sociological theory of disease. In this interview with Jansbøl and Johansen, Gannik primarily talks about the theoretical aspects of her work. Gannik’s theory of disease helps us reach a more precise understanding of connections between the two complex entities “disease” and “the social”. Gannik claims that disease is far more socially embedded than the health sector thus far has acknowledged, and she points out that factors outside of the health sector determine whether or not a person interprets some kind of physical discomfort as a symptom of disease severe enough to seek medical attention for. Even after a person has been transformed into a patient, many of his or her symptom-related actions are still more often determined by conditions in the home, at work, or among friends than it is by strictly medical matters. Gannik claims that the health sector hitherto has had an inadequate understanding of disease, because its spokespersons have defined it as a fundamentally biological entity which is largely unaffected by social conditions. In contrast, Gannik argues that disease can only be properly understood if one seriously takes into consideration the social lives of patients, inside the health sector, as well as outside it.